(untitled) (Texas Journal of Medical Science, 2024)
Irritable bowel syndrome (IBS) is a biopsyosociological disease that is not associated with organic intestinal changes. In total, 82 patients were investigated and 20 healthy contingent. Patients were made into two groups: the first group of patients with IBS that are divided into 2 small groups: IBSd (diarrhea) - 49 patients (26 men and 23 women) and IBSc (constipation) - 33 patients (15 men and 18 women). Abdominal pain was more often noted in patients with a clinical form of IBS with a predominance of diarrhea. Estimation of the severity of IBS symptoms allows to objectify the severity of clinical manifestation of intestinal dysfunction in patients, identify the clinical features of this pathology.